Cyber-Physical Social Media Platforms and Their Market Influence - Vindigni, Giovanni (European Journal of Applied Sciences, 2023)
Based on theories of political economy, this essay will examine existing power structures, which are based on proprietary strategies of industrial capitalism and have been transforming into a proliferating networked information economy, decentralizing individual action [1]. Over this course, the author will explain how infrastructural rearrangements modified markets from a considerably static manifestation towards multi-sided platforms, giving social media platforms power over intellectual property and trading informational goods on a transnational scale. In the second part of the essay, the author argues that, first, living in a neoliberalist system also embraces potential and liberal forces, affirming that technology is not the only influencing force in society [2]. However, the main focus of this part insists on resisting the dominance of platforms by exemplifying the far-reaching cultural, political, and institutional impacts of social networks on society. Finally, the author proposes possible future solutions of resistance to find an ethical and democratic way of balancing institutional, political, and cultural aspects to guarantee human freedom and development.